2016
DOI: 10.1001/jamaophthalmol.2016.1769
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Human Factors Immersive Simulation Training in Ophthalmology

Abstract: IMPORTANCE Human factors training can enhance teamworking and reduce error. It is used regularly in certain medical disciplines, but its use has not been established for ophthalmology to our knowledge. OBJECTIVE To explore the feasibility of providing immersive simulation human factors training for ophthalmic surgical teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…Confirmatory factor analysis can be used to test how well a sample of participant data fits the model by assessing whether items that are closely related in theory are highly intercorrelated in practice, forming distinct “factors” as expected. 76 The results should support the hypothesized number of factors, and the specific items that load onto each factor should make theoretical sense. For example, data from the SAQ suggested that its items could be categorized into 6 factors, which mapped onto the 6 components of patient safety the measure was designed to capture.…”
Section: Key Considerations For Choosing a Measurement Toolmentioning
confidence: 86%
See 1 more Smart Citation
“…Confirmatory factor analysis can be used to test how well a sample of participant data fits the model by assessing whether items that are closely related in theory are highly intercorrelated in practice, forming distinct “factors” as expected. 76 The results should support the hypothesized number of factors, and the specific items that load onto each factor should make theoretical sense. For example, data from the SAQ suggested that its items could be categorized into 6 factors, which mapped onto the 6 components of patient safety the measure was designed to capture.…”
Section: Key Considerations For Choosing a Measurement Toolmentioning
confidence: 86%
“…To provide a starting point for practitioners seeking suitable measurement tools, and to illustrate of some of the reliability and validity considerations outlined in this article, we present summaries of a range of measures that are potentially relevant for use in simulation-based healthcare improvement projects, and for which (in the case of healthcare-specific tools) validity evidence has been collected using samples of clinicians. These include measures of: nontechnical skills 4 , 5 , 39 , 48 , 49 , 52 , 58 60 , 76 , 77 , 80 117 (see Table 3, Supplemental Digital Content 1, which outlines 17 measures, http://links.lww.com/SIH/A516 ); technical skills and clinical performance 40 , 59 , 81 , 102 , 112 , 120 127 (see Table 4, Supplemental Digital Content 2, which outlines 6 measures, http://links.lww.com/SIH/A517 ); and psychological constructs 4 , 6 , 28 , 30 , 78 , 111 , 126 140 (see Table 5, Supplemental Digital Content 3, which outlines 7 measures, http://links.lww.com/SIH/A518 ).…”
Section: Key Considerations For Choosing a Measurement Toolmentioning
confidence: 99%
“…One study in this review, the Virtual Mentor e-learning programme, included cognitive components of cataract surgery training [ 141 ]. A pilot study by Saleh et al also demonstrated the feasibility of using high-fidelity, immersive simulation for cataract surgery, using scenarios based on previous patient safety incidents and evaluating the cross-validity and reliability of four established assessment tools (OTAS, NOTECHS, ANTS and NOTSS) [ 144 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saleh et al (2016) have noticeably demonstrated that simulation-based training of nontechnical skills, such as teamwork and communication, is also applicable in ophthalmology. Other competencies are equally important.…”
Section: Subtenon Injection 12mentioning
confidence: 99%
“…Other competencies are equally important. Saleh et al (2016) have noticeably demonstrated that simulation-based training of nontechnical skills, such as teamwork and communication, is also applicable in ophthalmology. Their findings are promising for further incorporation of simulationbased training of nontechnical skills in the future.…”
Section: Incision Of Dacryocystitis 25mentioning
confidence: 99%